ASEAN—A Regional Trade Pact Model for States in the Global South - Ronnie Gipson (Washington University Global Studies Law Review, 2021)
This article posits that the states in the Global South would benefit from the formation and implementation of the regional trade pact model by replicating the approach of the Association of Southeast Asian Nations (“ASEAN”). ASEAN utilizes the regional trade pact model to achieve an optimal balance between the pursuit of free trade principles in international trade policy juxtaposed against the perceived erosion of state sovereignty. As a result, free trade is sustainable as an anchor component of trade policy in the future, just in a modified form. An underlying premise that must be advanced to understand how free trade can thrive in today’s complicated global trading arena is that the benefits of free trade are best realized through the use of a Regional Trade Pact. Part I of this article sets the stage for the substantive discussion by expounding on the concept of free trade; a brief look at how nationalism threatens this economic principle; and the functioning of regional trade pacts. Part II of this article demonstrates how, in the short span of four decades, ASEAN has successfully implemented an overhaul of the member states’ domestic economies to include free trade principles. The end result of the long-term overhaul process is a stronger corps of states that enjoy economic success in the global trading arena because of (i) the maximization of domestic comparative advantage; and (ii) by leveraging bargaining power of the collective regional trade pact against states with significantly more trading muscle and resources. This article then connects the different themes to demonstrate that free trade in the international arena is sustainable and that it thrives when the optimal balance between promotion of trade and interference with domestic decision making is achieved. Finally, the article advances the notion that states within the Global South, that are regionally connected, would be well served by adopting the ASEAN model of a regional trade pact in order to improve their economies and trading positions within the global trading arena.